Spatiotemporal Analysis of COVID-19, AIDS, and SARS Epidemics across Maharashtra, Delhi, and West Bengal - Husam H. Abdulmughni,; Ratnadeep R. Deshmukh, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive study employs sophisticated geospatial analysis techniques to examine the intricate spatiotemporal distribution and temporal variations of COVID-19, AIDS, and SARS cases in Maharashtra, Delhi, and West Bengal. By meticulously mapping the occurrence and evolution patterns of these diseases, this research sheds light on the distinctive characteristics of the epidemic landscape in each region. The findings underscore the rapid spread of COVID-19, AIDS, and SARS in urban areas, particularly in states with megacities and densely populated urban slums, such as Delhi, Maharashtra, Tamil Nadu, and West Bengal. Additionally, these diseases show a heterogeneous geographical distribution within India, predominantly concentrating in central regions. Emphasizing the significance of understanding urban dynamics and population health characteristics in relation to disease transmission, this research contributes to a deeper understanding of the complex factors driving the spread of these diseases. Ultimately, this study provides insights that can inform the development of targeted interventions and strategies for initiative-taking of disease control, offering guidance to evidence-based decision-making and proactive public health management in the face of ongoing health challenges.
Keywords: COVID-19; SARS; HIV/AIDS; spatiotemporal; outbreaks; Maharashtra; Delhi; West Bengal; geographical information system; spatial clustering; GIS analysis